Notes on the Afrotropical hover fly genus Meromacroides Curran (Syrphidae, Eristalinae) - Bellingan, T.; Midgley, J.; Goergen, Georg E.; Jordaens, K. (Pensoft Publishers, 2021)
The African endemic hover fly Meromacroides meromacriformis (Bezzi, 1915) (Syrphidae, Eristalinae) was described more than a century ago and its monotypic status established in 1927, but subsequent collections and publications are rare. Only the male has been described and nothing is known about its biology. We re-describe the male, including geographic variation, describe the female for the first time and provide the first DNA barcodes for the species. Despite the large range and observed variations, there is insufficient evidence to describe additional taxa in the genus. Biological observations are presented, which may shed some insight into this rare and enigmatic hover fly, whose known distribution now spans the Afrotropical Region.